Application of Photography Composition Techniques on Instagram Account @11xn_d Kun WayV Photo Work - Afifah, Nazwa (Bina Nusantara University, 2025)
Photography is not merely the act of capturing images using a camera or smartphone. It is a creative process that involves both technical and aesthetic considerations, one of which is composition. Composition plays a crucial role in the field of photography by creating visually appealing images with strong visual value. This research explores the application of photographic composition techniques in the works of Kun WayV, shared on the Instagram account @11xn_d. The photographs indirectly implement compositional principles such as the rule of thirds, leading lines, framing, and points of interest. Employing a qualitative approach, this study utilizes literature review and social media observation as data collection techniques. A descriptive-narrative writing method is used to convey the research findings and communicate the significance of composition in contemporary photographic practice.